A Case Study of the Reception of Aristotle in Early Protestantism: The Platonic Idea of the Good in the Commentaries on the Nicomachean Ethics - Herreros, Alfonso (Renaissance and Reformation / Renaissance et Réforme, 2020)
The present article examines the philosophical ethics of Protestants teaching in higher education during the sixteenth and seventeenth centuries and their reception of Aristotle’s Nicomachean Ethics, 1.6. Two theses are illustrated. First, the survey of fourteen commentaries shows clear parallels with the medieval interpretation of the Ethics, which the Protestant authors creatively expanded. Thus, the continuity of Protestantism with the earlier tradition of Christian philosophy is substantiated in this specific case for a representative group of authors. Second, over against the prejudices according to which Protestantism simply censured ethics and subsumed it into moral theology, this article shows that, in truth, Aristotle was still the fundamental philosophical reference in a topic as central as the definition of happiness, and that the Platonic “theological” alternative was not considered appropriate for a philosophical discipline.